Neonatal near miss and mortality: factors associated with life-threatening conditions in newborns at six public maternity hospitals in Southeast Brazil - Pauline Lorena Kale; Maria Helena Prado de Mello-Jorge; Kátia Silveira da Silva; Sandra Costa Fonseca
Abstract: We aimed to evaluate factors associated with cases of neonatal near miss and neonatal deaths at six public maternity hospitals in São Paulo and Rio de Janeiro States, Brazil, in 2011. A prospective hospital-based birth cohort investigated these outcomes among live births with life-threatening conditions. Associations were tested using multinomial logistic regression models with hierarchical levels. High rates of near miss were observed for maternal syphilis (52.2‰ live births) and lack of prenatal care (80.8‰ live births). Maternal black skin color (OR = 1.9; 95%CI: 1.2-3.2), hemorrhage (OR = 2.2; 95%CI: 1.3-3.9), hypertension (OR = 3.0; 95%CI: 2.0-4.4), syphilis (OR = 3.3; 95%CI: 1.5-7.2), lack of prenatal care (OR = 5.6; 95%CI: 2.6-11.7), cesarean section and hospital, were associated with near miss; while hemorrhage (OR = 4.6; 95%CI: 1,8-11.3), lack of prenatal care (OR = 17.4; 95%CI: 6.5-46.8) and hospital, with death. Improvements in access to qualified care for pregnant women and newborns are necessary to reduce neonatal life-threatening conditions.